2017
DOI: 10.18869/acadpub.jhl.2.2.73
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Health Literacy of Medical and Dentistry Students of Rafsanjan University of Medical Sciences in 2016

Abstract: * Msc in knowledge and information science , dental school, Rafsanjan university of medical science, Rafsanjan, Iran. (Corresponding Author) Email: shakibae7@gmail.com Maryam SalamiAssistant professor in knowledge and information science, Faculty of Education and Psychology, Payame Noor University Mashhad branch, Mashhad, Iran. Received ABSTRACTBackground and objective: Health literacy represents an individual's capacity to acquire, interpret and understand the information necessary for the required services … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…12 Sharif Moghadam also reported that post-basic sciences students had higher health literacy than pre-basic sciences students. 23 The reason is probably studying more in the fields of health, after the Basic sciences and obtaining more information. Therefore, academic seniority is an effective factor in students' health literacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Sharif Moghadam also reported that post-basic sciences students had higher health literacy than pre-basic sciences students. 23 The reason is probably studying more in the fields of health, after the Basic sciences and obtaining more information. Therefore, academic seniority is an effective factor in students' health literacy.…”
Section: Discussionmentioning
confidence: 99%
“…25 Regarding marital status, the results of Sharif-Moghadam's study showed that married students had higher averages than single students in every aspect of health literacy. 23 This is probably due to having married life and being responsible for the health of family members. In the present study, the reason for the insignificance of marital status is probably the small number of married people.…”
Section: Discussionmentioning
confidence: 99%
“…Given the significant increase in the student population in Iran in recent years, it is important to identify effective factors that could familiarize students with healthy behaviors and keep them away from risky behaviors [13]. Identifying these factors could assist health planners and executives to further improve health promotion programs and make optimal use of health services [1].…”
Section: Introductionmentioning
confidence: 99%
“…Given the signi cant increase in the student population in Iran in recent years, it is important to identify effective factors that could familiarize students with healthy behaviors and keep them away from risky behaviors [13]. Identifying these factors could assist health planners and executives to further improve health promotion programs and make optimal use of health services [1].…”
Section: Introductionmentioning
confidence: 99%